2022
DOI: 10.1021/acs.cgd.1c01201
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Pentamidine in Carboxylated Pillar[5]arene: Late Sequential Crystallization and Diversity of Host–Guest Interactions

Abstract: Here we describe the inclusion of the minor-groove binding drug pentamidine in its extended conformation into the macrocyclic cavity of water-soluble carboxylated pillar[5]arene. The artificial host−guest system is manifested as an ensemble of three crystalline forms differing in the pillar[5]arene−pentamidine interaction mode, solvation type, and even stoichiometry. The strong hydrogen bonds of various types of amidinium−carboxylate (between pentamidine and pillar[5]arene) and carboxylic− carboxylate (between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…The 1:1 complex of CPA6 with dMV represents a classical inclusion associate, similar to that earlier reported for the CPA5 - PTM complex, in which the guest molecule is trapped in the host cavity by multiple and cooperative intra- (carboxylic-carboxylate) and intermolecular (carboxyl­(ate)-pyridinium cation) hydrogen bonds. A partial loss of symmetry of the complex is observed due to the greater flexibility of CPA6 compared to CPA5 : the plane of one of the aromatic rings is deflected with respect to the planes of the other rings, resulting in a conformational distortion and inclination of the entire complex.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…The 1:1 complex of CPA6 with dMV represents a classical inclusion associate, similar to that earlier reported for the CPA5 - PTM complex, in which the guest molecule is trapped in the host cavity by multiple and cooperative intra- (carboxylic-carboxylate) and intermolecular (carboxyl­(ate)-pyridinium cation) hydrogen bonds. A partial loss of symmetry of the complex is observed due to the greater flexibility of CPA6 compared to CPA5 : the plane of one of the aromatic rings is deflected with respect to the planes of the other rings, resulting in a conformational distortion and inclination of the entire complex.…”
supporting
confidence: 84%
“…In our further solid state structural studies CPA5 has shown its ability to complex viologen derivatives and to form coordination polymers with alkali-earth cations . Recently, we have demonstrated the rich host–guest chemistry of CPA5 -pentamidine crystal complexes highlighting the role of amidinium-carboxylate hydrogen bonding and cavity inclusion …”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The main objective of this part of the study was the detailed structural characterization of the noncovalent complexes in the mother solutions from which the crystals grew, whereby identifying similarities and the differences between solid phase and solution/gas-phase chemistry . This unique insight into the precrystallization process using the IM-MS approach has been successfully applied previously to characterize several host–guest complexes with CPA5 and CPA6 , providing evidence of their distinct primary conformational ordering in mother solutions.…”
Section: Introductionmentioning
confidence: 99%